Proses Asuhan Gizi Terstandar pada Pasien Diabetes Mellitus Tipe 2 dengan Hipertensi: Diet Rendah Karbohidrat, Gula, dan Garam - Erwanda Anugrah Permatasari; Qonita Rachmah; Avilla Arsa (Media Gizi Kesmas, 2022)
Background: Type 2 diabetes mellitus patients require special nutrition care to reduce levels of blood sugar, recovery, and adequate nutrition intake. Especially in the case of type 2 diabetes mellitus patients with hypertension that affects appetite and the ability to consume food adequately. The nutrition care process was done by providing a low carbohydrate, sugar, and salt diet to reduce levels of blood sugar and blood pressure, and prevent unexpected weight loss. Objectives: To knowing the nutrition care process to type 2 diabetes mellitus patients with hypertension which apply a low carbohydrate, sugar, and salt diet. Methods: This study was conducted in November 2021 in hospitalized patients of RS X Sidoarjo. Results: After the nutrition intervention, the patient's condition began to improve, marked by most of the intake can reach target (>80%), the results of the biochemical laboratory such as random blood sugar, creatinine, and sodium showed a decrease and increase to normal values, but there are still symptoms that are felt even though they have decreased in scale such as nausea, difficulty chewing, and defecation. Conclusions: In this case, recovery of the patient's condition is quite fast. Appetite and the ability to consume food gradually improve, marked by the food waste can reach target (<30%). Overall, the nutrition intervention provided was achieved.